The THE AMPHIBIANS AND REPTILES IN KOMODO NATIONAL PARK AND THE SURROUNDING AREA - Umar Fhadli Kennedi; Mirza Kusrini; Ani Mardiastuti; Achmad Ariefiandy (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
The Komodo National Park in the Wallacea region is the komodo dragon’s primary habitats. Published report on the herpetofauna of this national park is mostly concentrated in Komodo island. To increase our knowledge of amphibian and reptile communities in Komodo National Park, we conducted a herpetofauna survey in Komodo and Rinca Island and the nearby coastal area to assess diversity and community similarity and developed a complete checklist of the herpetofauna of Komodo National Park. We conducted a Visual Encounter Survey and put glue traps from February-April 2018 at six locations on Komodo Island (Loh Liang, Loh Wau dan Komodo Village) and Rinca Island (Loh Buaya, Loh Baru, and Rinca Village); and three locations on coastal areas of Flores (Labuan Bajo and Cumbi Village) and coastal area of Sumbawa (Sape) adjacent to Komodo National Park. We found seven species of amphibians and 22 species of reptiles and, however, only two species of amphibians and 18 species of reptiles were found in Komodo and Rinca Island. The highest diversity (H’ = 2.14) is in Loh Buaya (Rinca Island), and the highest evenness (E=0.58) is in Loh Baru (Rinca Island). The highest similarity occurs between Komodo Island and Rinca Island (IS = 0.8). Using data from other research, we have compiled a list of four species of amphibians and 39 species of reptiles occurring at three main islands of Komodo National Park: Komodo island, Rinca Island and Padar Island. Keywords: Herpetofauna diversity, Komodo National Park, Lesser Sunda Islands